Beers and blurred boundaries: The spatial and gendered organisation of pre-match venues for English football fans. (September 2020) - Richards, Jessica; Parry, Keith D.
Academic research into sports fans has grown in recent years with studies examining a variety of aspects associated with fandom. However, recent changes in the professionalisation and commercialisation of sport have resulted in the creation of new spaces for fan experiences. In this article, we examine one of these created spaces, the fan zone. Through a case study on matchgoing fans from Everton Football Club we explore how this new space sits alongside traditional pre-match gathering places such as the 'pub' and examine the gendered organisation of these spaces. Drawing on Bale's concept of boundaries within sports fan communities we show that traditional venues for pre-match activities enhance, maintain and legitimise masculine boundaries within sports fandom. We argue that fan zones provide an alternative match day atmosphere and experience that is centred on a family-friendly or at least family-inclusive culture.